Studying Impacts of Urban Impermeability on Fear of Crime Using the Space Syntax Method; The Kuruçeşme Neighborhood as the Case Study - Meysam Soleimani; Maryam Golabi (Urban Science)
The complex relationship between crime and urban permeability is evident in the models of CPTED. Access restriction has been considered as a design strategy to reduce crime rates. The present study investigates the impact of impermeability on fear of crime in Kuruçeşme, a historic neighborhood in Bursa. Space Syntax is applied to evaluate the configurational relationship between the neighborhood and the city through correlation analysis of connectivity (local) and integration (global) measures. By choosing the least correlated segments in the scatter plot diagram, two incompatible areas are identified: areas with “excessive permeability” (locally permeable with low global accessibility) and areas with “severe impermeable” (globally accessible with low local permeability). These areas are assessed through semi-structured, in-depth interviews, allowing inhabitants to express their thoughts about and experiences of the fear of victimization. The findings reveal that physical cues perceived as signs of danger are different in public areas characterized with excessive permeability or severe impermeability. The former suffers from a lack of “natural surveillance” and physical disorders, while the latter engenders extreme “territoriality”, resulting in social incivilities. The research underscores that urban impermeability heightens the fear of victimization by changing the configurational features of a neighborhood and manipulating mechanisms of crime prevention.